2020
DOI: 10.1021/acs.jpcc.0c07613
|View full text |Cite
|
Sign up to set email alerts
|

Shedding Light on the Interfacial Structure of Low-Coverage Alkanethiol Lattices

Abstract: A comprehensive description of the self-assembly process of alkanethiols on Au( 111) is presented, focused on the initial formation of the lying down phases. Low-coverage monolayers are prepared by the disintegration of Au 144 (RS) 60 nanoclusters on the reconstructed (22 × √3)-Au(111) surface.The method provides a limited number of thiols together with a large excess of gold adatoms. Scanning tunneling microscopy and density functional theory calculations were employed to study the transition between low to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…This finding was also reported in previous theoretical studies . In addition, the phenomenon that a gold atom being pulled up by the thiol terminal as a result of Au–S bond formation mimics the adatom model used to explain the experimental observations regarding self-assembly of thiolates on Au(111). …”
Section: Resultssupporting
confidence: 84%
“…This finding was also reported in previous theoretical studies . In addition, the phenomenon that a gold atom being pulled up by the thiol terminal as a result of Au–S bond formation mimics the adatom model used to explain the experimental observations regarding self-assembly of thiolates on Au(111). …”
Section: Resultssupporting
confidence: 84%
“…Our experimental data indicate that the AuNCs protected by RS-Au-SR units decompose into Au islands and LD phases containing RS-Au-SR moieties upon interaction with the Au surface. We have recently shown that the most stable configurations for H-T and H-H phases are described, in both cases, by a (8 × 2√3) rect unit cell . The optimized structures are shown in Figure a,b, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…We have recently shown that the most stable configurations for H-T and H-H phases are described, in both cases, by a (8 × 2√3) rect unit cell. 43 The optimized structures are shown in Figure 2a,b, respectively.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…24,25,36 More recently, van der Waals interactions between the molecular chains were also included in the DFT models with various functions. 20,[40][41][42][43][44] The considered supercells aiming to describe the SAM on gold are usually rather small in order to significantly reduce the computational cost, thus restricting the exploration of the complex relative conformations and orientations of the co-adsorbed molecules in long range. In addition, under experimental conditions the presence of contaminants adds a supplemental and hardly incontrollable dipole contribution that blurs the WF values.…”
Section: Introductionmentioning
confidence: 99%